A Dramatic Disappearance - Deutsch, Stacia (Chicago, Illinois : Albert Whitman, 2023)
When a traveling theater production comes to town, Jessie is excited to write a profile of its star, but when the performer goes missing days before the show is set to make its debut, Jessie realizes that something big is going on behind the scenes.
Keywords: Student newspapers and periodicals -- Juvenile fiction; Theater -- Juvenile fiction; Missing persons -- Juvenile fiction; Student newspapers and periodicals -- Fiction; Theater -- Fiction; Missing persons -- Fiction; Detective and mystery fiction; School fiction